2019
DOI: 10.1186/s13104-019-4419-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unintended pregnancy among women attending antenatal care in Maichew Town, Northern Ethiopia, 2017

Abstract: Objective Unintended pregnancy is one of the most public health issues in the world, and it is the major sexual and reproductive health problem which carries a higher risk of morbidity and mortality for women, often due to unsafe abortion. Even though family planning services are effective and available than ever before, unintended pregnancy and unsafe abortion are the major public health problems in the study area. Therefore, this study aimed at assessing the magnitude and associated factors of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
34
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 16 publications
13
34
3
1
Order By: Relevance
“…In this study, 92.7% of the mothers had a planned pregnancy. This study finding was higher than the report from Maichew town (70.3%), West Belessa Woreda (86.3%) and Denmark (77%) (Backhausen et al, ; Kassahun et al, ; Tsegaye, Mengistu, & Shimeka, ). This might be due to difference in the use and accessibility of family planning services.…”
Section: Discussioncontrasting
confidence: 63%
“…In this study, 92.7% of the mothers had a planned pregnancy. This study finding was higher than the report from Maichew town (70.3%), West Belessa Woreda (86.3%) and Denmark (77%) (Backhausen et al, ; Kassahun et al, ; Tsegaye, Mengistu, & Shimeka, ). This might be due to difference in the use and accessibility of family planning services.…”
Section: Discussioncontrasting
confidence: 63%
“…Studies conducted in different African countries identified that age, place of residence, marital status, ethnicity, types of employment, educational status, numbers of living children, monthly income and women autonomy, parity, gravidity, knowledge on contraceptives, accessibility of contraceptives as determinants of unintended pregnancy (8)(9)(10)(11)20). Similarly, studies conducted in various parts of Ethiopia identified age, residence, religion, marital status, parity, visiting health professionals, history of abortion, age at first birth, family size, educational status, gravidity, distance from health facility, history of still birth and knowledge on modern contraceptive methods as determinants of unintended pregnancy (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 98%
“…According to studies conducted in different parts of Ethiopia, the prevalence of unintended pregnancy ranged from 13.7%to 41.5%. In addition, the prevalence of unintended pregnancy in Ethiopia based on study in 2011 EDHS was 32% (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In this study married respondents were more likely to have pregnancy compared to respondents who were not married. Unlike studies done in antenatal care unit shows being unmarried was potential exposing factor for unintended pregnancy (2,3,12,14,28,29,32,33). This might be due to respondents who were not married may not have sexual contact in turn they could not have unintended pregnancy.…”
Section: Discussionmentioning
confidence: 86%